2021
DOI: 10.1111/add.15385
|View full text |Cite
|
Sign up to set email alerts
|

Trends in electronic cigarette use and conventional smoking: quantifying a possible ‘diversion’ effect among US adolescents

Abstract: Background and aims The impact of electronic cigarettes (ECs) on nicotine use is hotly debated: some fear that ECs are a 'catalyst' to conventional smoking, while others argue that they divert adolescents from the more harmful product. This study used simulation modeling to evaluate the plausibility of catalyst and diversion hypotheses against real-world data. Design A simulation model represented life-time exclusive EC use, exclusive conventional smoking and dual use as separate subpopulations. The 'catalyst'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
(48 reference statements)
2
19
0
Order By: Relevance
“…Figures 6 and 7 do not conclusively prove a diversion effect, but they do show that population-level trends are much better explained by a net diversion effect, and are very inconsistent with a net catalyst effect. Recently, this was also observed for the trends in e-cigarette use among young persons in the US (Selya & Foxon, 2021).…”
Section: User Pattern Of Snussupporting
confidence: 58%
“…Figures 6 and 7 do not conclusively prove a diversion effect, but they do show that population-level trends are much better explained by a net diversion effect, and are very inconsistent with a net catalyst effect. Recently, this was also observed for the trends in e-cigarette use among young persons in the US (Selya & Foxon, 2021).…”
Section: User Pattern Of Snussupporting
confidence: 58%
“…[118][119][120][121] smoke. [122][123][124] Conversely, some prospective studies have found the vaping-smoking relationship strongest in youths at low risk of smoking. [125][126][127] Obvious plausible correlates are often not considered, however.…”
Section: Vaping Causing Smoking Initiationmentioning
confidence: 99%
“…The potential role of e‐cigarette trends in explaining the current findings is unclear. It remains a matter of active debate whether e‐cigarette use causes later cigarette smoking, 26 whether both behaviors originate from a common liability for tobacco use, 27 or whether e‐cigarette use diverts youth away from cigarette smoking 28 . Even less is certain about this question in the context of rurality, and this a critical topic for ongoing research.…”
Section: Discussionmentioning
confidence: 99%